Yield and N use efficiency of wheat as influenced by bed planting and N application - Khaleque, MA; Paul, NK; Meisner, Craig A (Bangladesh Journal of Agricultural Research, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Wheat (Triticum aestivum L.) was planted as winter crop using raised bed and conventional planting system with four N levels at Regional Wheat Research Station, Rajshahi (latitude 28Â°75â² N and longitude 92Â°58â² E), during November to March in 2002 and 2003 to study N content in grain and straw, uptake of total nitrogen, N use efficiency, fertilizer recovery percentage and grain yield. The highest N content in grain and straw were obtained from bed planting system with Shatabdi at 150% N treatment. Maximum total N uptake by the plants was found in bed elevation as compared to conventional planting system. The highest N use efficiency was observed at N zero treatment as compared to applied N levels. Shatabdi noticed highest N use efficiency among the crop varieties. The maximum fertilizer recovery percentage was noted in Shatabdi under bed planting system. The highest grain yield (2,555 kg/ha) was produced from bed planting system. Significantly the highest grain yield (2,929 kg/ha) was found in Shatabdi. The highest grain yield (3,746 kg/ha) was found when 150% N was applied. In bed planting system, the highest grain yield (3,323 kg/ha) was produced when 150% N was applied. The lowest grain yield (1,177 kg/ha) was obtained in zero N treatment. Among the varieties, Shatabdi was the best performer in bed planting system due to maximum nitrogen and protein content in grain and straw, maximum N use efficiency and fertilizer recovery percentage. Key Words: Bed planting, N content, N use efficiency and fertilizer recovery percentage. doi:10.3329/bjar.v33i3.1603 Bangladesh J. Agril. Res. 33(3) : 439-448, September 2008